Comparison of Descriptor- and Fingerprint Sets in Machine Learning Models for ADME-Tox Targets - Orosz, Álmos; Héberger, Károly; Rácz, Anita (Frontiers in Chemistry, 2022)
The screening of compounds for ADME-Tox targets plays an important role in drug design. QSPR models can increase the speed of these specific tasks, although the performance of the models highly depends on several factors, such as the applied molecular descriptors. In this study, a detailed comparison of the most popular descriptor groups has been carried out for six main ADME-Tox classification targets: Ames mutagenicity, P-glycoprotein inhibition, hERG inhibition, hepatotoxicity, blood-brain-barrier permeability, and cytochrome P450 2C9 inhibition. The literature-based, medium-sized binary classification datasets (all above 1000 molecules) were used for the model building by two common algorithms, XGBoost and the RPropMLP neural network. Five molecular representation sets were compared along their joint applications: Morgan, Atom-pairs and MACCS fingerprints and the traditional 1D, 2D molecular descriptors, as well as 3D molecular descriptors, separately. The statistical evaluation of the model performances was based on 18 different performance parameters. Although all the developed models were close to the usual performance of QSPR models for each specific ADME Tox target, the results clearly showed the superiority of the traditional 1D, 2D, and 3D descriptors in case of the XGBoost algorithm. It is worth to try the classical tools in single model building, because the use of 2D descriptors can produce even better models for almost every dataset, than the combination of all the examined descriptor sets.